Can single-sign-on improve password management? A focus group study - Katuk, Norliza; Mohamad Tahir, Hatim; Zakaria, Nur Haryani; Halim, Mohamad Subri (2014)
This paper presents a research concerning password management and single-sign-on for accessing lnternet applications.Many lnternet applications require users to subscribe to their services and authenticate themselves through the use of login credentials.The number of such applications is increasing exponentially which caused ineffective login credentials management among users.This study was conducted with two objectives (i) to identify how users manage their usernames and passwords, and (ii) to examine whether users see the benefits of single-sign-on.To achieve these objectives, a focus group interview was conducted on students from a local university.The results of the study suggested that the students did not practice proper password management.Further, it suggested that single-sign-on may not be the immediate solution to improve the students' password management.